Demographics and follow up of post partum intra-uterine copper device in tertiary hospital in Delhi, India - Garg, Nidhi; Sarkar, Bani; Singla, Saloni; Meena, Rajesh Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Increasing unintended pregnancies in post partum females in our country warrants urgent attention towards prevalence and efficacy of contraceptives used. This study was done to determine the prevalence of PPIUCD and its follow up in patients attending tertiary hospital in New Delhi, India. Methods: Prospective study was carried in Department of Obstetrics and Gynecology, Dr. RML Hospital, New Delhi, India over a period of 1 year from July 2017 to July 2018. The awareness and prevalence of PPIUCD was assessed. At 6 week follow-up visit, women with PPIUCD were asked for symptoms of unusual vaginal discharge, irregular or heavy bleeding per vagina, and any expulsions if noticed. All the data was recorded and assessed. Results: Out of 1478 deliveries, 1372 were eligible for PPIUCD. 335 patients got PPIUCD inserted. 295 patients were followed as 40 patients were lost to follow up. 79.3% women did not have any complaints. 11.8%, 1% and 7.4% women had only heavy menstrual bleeding, only lower abdominal pain and both symptoms respectively. Spontaneous expulsion rate was noted in one patient (0.3%) at 6 weeks. IUCD removal was done in 4 patients who had complaints of pain and heavy menstrual bleeding not conservatively managed. Conclusions: PPIUCD insertion is a safe, convenient and effective method of contraception. The benefits of contraception immediately after delivery outweigh disadvantage of complications. Antenatal counseling and follow up in hospitals need to be strengthened to increase awareness and acceptability of PPIUCD.